Feature issue introduction : halide perovskites for optoelectronics - White, Thomas P. (2019)
This joint Optics Express and Optical Materials Express feature issue presents a collection of nine papers on the topic of halide perovskites for optoelectronics. Perovskite materials have attracted significant attention over the past four years, initially for their outstanding performance in thin film solar cells, but more recently for applications in light-emitting devices (LEDs and lasers), photodetectors and nonlinear optics. At the same time, there is still much more to learn about the fundamental properties of these materials, and how these depend on composition, processing, and exposure to the environment. This feature issue provides a snapshot of some of the latest research in this rapidly-evolving multidisciplinary field.